Female Sexual Function Index in Perimenopause Women After Loving Yoga Intervention in Yogyakarta - Setyani, Rizka Ayu (-)
During perimenopause, females experience decreased sexual function. Loving yoga has a focus of movement on the pelvic muscles is a complementary therapy to overcome such complaints. The purpose of this study was to analyze the large influence of the sexual function index of perimenopause women simultaneously and partially after doing loving yoga. Quantitative research with the cross-sectional design was conducted from April to June 2020 in Yogyakarta. Purposive sampling in women aged 40-50 years, sexually active, and having a sexual dysfunction. The data was collected through a Female Sexual Function Index (FSFI) questionnaire and then tabulated and scoring. Data analysis in univariate and multivariate using linear regression analysis multiple partial t-tests and simultaneous F test. The results stated that there is a simultaneous and partial influence on sexual function (Sig value. < 0.05), with great influence on sexual interest (16,541%), sexual arousal (15,289%), lubrication (18,233%), orgasm (16,036%), sexual satisfaction (16,330%), and dyspareunia (17,586%). In conclusion, loving yoga can improve the sexual function of perimenopause women. Therefore, it is recommended that this exercise can be done regularly to get the optimal effect.